Lubitsch in Berlin: Fairy-Tales, Melodramas, and Sex Comedies - Lubitsch, Ernst; Sparkuhl, Theodor; Waschneck, Kurt; Wagner, Fritz A.; Oswalda, Ossi; Janson, Victor; Wegener, Paul; Porten, Henny; Negri, Pola (The Masters of Cinema Series, 2017)
Before he arrived in Hollywood to leave his indelible (and inimitable) mark on timeless comedies like "Trouble in Paradise" and "The Shop Around the Corner", Ernst Lubitsch created an expansive body of work in Germany that proved to be as varied in its tone as it was sophisticated in its measure of man and woman. This set collects six recently restored works from the silent phase of Lubitsch's career, and casts new light on the director both as a fully-formed comic master, and as a virtuoso of cinematographic technique. [Cover]